Elevated Maternal Soluble Gp130 and IL-6 Levels and Reduced Gp130 and SOCS-3 Expressions in Women Complicated With Preeclampsia - Wang, Yuping (2010)
Increased inflammatory response plays a significant role in the vascular pathophysiology in preeclampsia. However, the mechanism for increased inflammatory response in preeclampsia is largely unknown. Interleukin (IL)-6 levels are elevated in women with preeclampsia. IL-6 and its receptors, IL-6R and glycoprotein (gp)130, play a critical role in mediating antiinflammatory response via induction of SOCS-3 (suppressor of cytokine signaling-3). However, IL-6 receptor levels and expressions have not been studied in preeclampsia. In this study, we measured IL-6 and its 2 soluble receptors, soluble IL-6R and soluble gp130, in maternal plasma from normal and preeclamptic pregnant women and found that not only IL-6 but also soluble gp130 levels were significantly higher in preeclamptic women than in normotensive pregnant controls. We further examined IL-6R, gp130, and SOCS-3 expressions in maternal vessels and leukocytes and found that gp130 and SOCS-3 expressions were downregulated in both vessel endothelium and leukocytes from preeclampsia. Different patterns for IL-6R and gp130 expressions were found. IL-6R expression was also downregulated in leukocytes from preeclampsia. Our results suggest that increased plasma soluble gp130/soluble IL-6R/IL-6 ratio and reduced membrane transsignaling gp130 expression could contribute to decreased SOCS-3 expression and subsequent reduction in SOCS-3 antiinflammatory activity in women with preeclampsia. Thus, reduced gp130 and SOCS-3 expressions may offer, at least in part, a plausible explanation of reduced antiinflammatory protection in the maternal vascular system in preeclampsia.